Morphological Assessment of Megakaryocytes in Bone Marrow Aspirates in Different Hematological Conditions: A Descriptive Observational Study from a Tertiary Care Centre in Jaipur - Dr. Neelam Meena; Dr. Priti Saini; Dr. Yashvi Gehlot; Dr. Rinku Saini; Dr. Lovesh Saini, (International Journal of Pharmacy Research & Technology (IJPRT), 2026)
Background: Megakaryocytes play a pivotal role in thrombopoiesis, and alterations in their morphology provide valuable diagnostic information in a wide spectrum of hematological disorders. Although bone marrow aspiration is routinely performed for the evaluation of cytopenias and hematological malignancies, the diagnostic significance of megakaryocyte morphology across different disease entities remains underexplored. Methods: A descriptive observational study was conducted in the Department of Pathology, SMS Medical College, Jaipur, including 150 consecutive bone marrow aspiration specimens from patients with various hematological disorders. Bone marrow aspirates were evaluated for marrow cellularity, megakaryocyte number, and qualitative morphological alterations. Morphological abnormalities were categorized as dysplastic, non-dysplastic, or mixed. Clinical findings and hematological diagnoses were correlated with megakaryocyte morphology using appropriate statistical analysis, with a p-value <0.05 considered statistically significant. Results: Of the 150 cases, 100 (66.7%) were neoplastic and 50 (33.3%) were non-neoplastic disorders. Hypercellular marrow was observed in 55.3% of patients. Altered megakaryocyte morphology was identified in 90.0% of cases, with mixed morphological changes being the most frequent pattern (45.3%). Hypolobulated megakaryocytes (50.0%), immature forms (36.7%), and micromegakaryocytes (35.3%) were the predominant abnormalities. Dysplastic megakaryocyte features were significantly more common in neoplastic disorders than in non-neoplastic disorders (87.0% vs. 48.0%, p<0.001). Megakaryocyte number also demonstrated significant variation across different hematological diagnoses. Conclusion: Systematic evaluation of megakaryocyte number and morphology during bone marrow aspiration provides important diagnostic information and significantly improves differentiation between reactive and neoplastic hematological disorders. Megakaryocytic assessment should be considered an integral component of routine bone marrow examination.